Probiotic potential and technological properties of lactic acid bacteria isolated from Minas Frescal cheese - Silva, Bruna Vieira da; Souza, Bárbara Caliane de Oliveira; Muricy, Mile Ane Larissa Costa; Ribeiro, Milena Gabriel; Reis, Clarita Silveira; Jesus, Márcia Araujo de; Evangelista-Barreto, Norma Suely (Revista JRG de Estudos Acadêmicos, 2025)
Lactic acid bacteria (LAB) are recognized for their biotechnological and industrial potential, particularly due to the production of bacteriocins, organic acids, and hydrogen peroxide, compounds associated with antimicrobial activity and applicable as natural preservatives. The isolation of LAB from foods, especially milk and dairy products, is strategic for the development of new probiotic products. This study investigated the occurrence and probiotic potential of LAB isolated from Minas Frescal cheese. Biochemical identification included Gram staining, catalase test, gas production from glucose, arginine hydrolysis, and growth under different temperatures and NaCl concentrations. Probiotic and technological assessments included inhibition assays against Staphylococcus aureus and Escherichia coli, tolerance to acidic pH values (7.0, 3.0, and 2.5), and bile salt concentrations (0.3 - 0.7%), as well as analyses of enzymatic and metabolic activity. All isolates were Gram-positive, catalase-negative, and mostly belonged to the genus Leuconostoc (73.3%). Regarding antimicrobial susceptibility, 96.6% of the isolates were sensitive to ampicillin, and 3.3% were sensitive to imipenem. Strong inhibitory activity was observed against S. aureus and E. coli; however, the cell-free supernatant did not exhibit antagonistic effects. Most strains (96.6%) survived at pH 2.5, and all tolerated bile salts. High proteolytic activity (>97%) was detected, whereas production of diacetyl, capsule, lipase, and hydrogen peroxide was absent. Lactic fermentation occurred in 96.6% of the strains, characterized by the formation of a gel. In conclusion, LAB isolated from Minas Frescal cheese exhibited promising probiotic and technological properties, highlighting their potential application in functional foods with benefits for gut health and food safety.”